The Effect of Fiberglass Paint Coating on the Shear and Flexural Strength of Concrete Blocks - Juliafad, Eka; Restu, Lisyana Junelin; Yusmar, Fajri; Sandra, Nevy; Putra, Rusnardi Rahmat (Civil Engineering Journal, 2025)
This study uses an experimental method to investigate the behavior of concrete blocks coated with fiber paint, focusing on their shear and flexural strength, ductility, stiffness, and energy dissipation to enhance their mechanical performance. The fiber paint coatings used in this study were applied in different thicknesses, namely 1 mm, 2 mm, and 3 mm. The results show that a 3 mm coating provided the highest improvement, with shear and flexural strengths increasing by 47.36% and 66.06%, respectively. Flexural ductility improved by up to 32%, while stiffness increased by 12% in flexure and 13% in shear. Energy dissipation also showed significant enhancement; total flexural energy increased from 1.38 kNmm to 10.76 kNmm at 3 mm, and shear energy dissipation reached 50.72 kNmm at 3 mm. These results confirm that fiber paint can enhance the shear and flexural strength, ductility, stiffness, and energy dissipation of concrete blocks. This study introduces fiber paint as a practical reinforcement method for concrete block materials, offering a simple, easy-to-apply, and cost-effective alternative that improves both mechanical and aesthetic performance.